Primeval very low-mass stars and brown dwarfs – III. The halo transitional brown dwarfs. Issue 1 (23rd May 2018) - Zhang (张曾华), Z H; Pinfield, D J; Gálvez-Ortiz, M C; Homeier, D; Burgasser, A J; Lodieu, N; Martín, E L; Zapatero Osorio, M R; Allard, F; Jones, H R A; Smart, R L; López Martí, B; et al.
ABSTRACT: We report the discovery of an esdL3 subdwarf, ULAS J020858.62+020657.0, and a usdL4.5 subdwarf, ULAS J230711.01+014447.1. They were identified as L subdwarfs by optical spectra obtained with the Gran Telescopio Canarias, and followed up by optical-to-near-infrared spectroscopy with the Very Large Telescope. We also obtained an optical-to-near-infrared spectrum of a previously known L subdwarf, ULAS J135058.85+081506.8, and reclassified it as a usdL3 subdwarf. These three objects all have typical halo kinematics. They have T eff around 2050–2250 K, −1.8 ≤ [Fe/H] ≤ −1.5, and mass around 0.0822–0.0833 M⊙, according to model spectral fitting and evolutionary models. These sources are likely halo transitional brown dwarfs with unsteady hydrogen fusion, as their masses are just below the hydrogen-burning minimum mass, which is ∼ 0.0845 M⊙ at [Fe/H] = −1.6 and ∼ 0.0855 M⊙ at [Fe/H] = −1.8. Including these, there are now nine objects in the 'halo brown dwarf transition zone', which is a 'substellar subdwarf gap' that spans a wide temperature range within a narrow mass range of the substellar population.